Evaluation of repulsive particle swarm method for phase equilibrium and phase stability problems - Rahman, Imran; Das, Anwesh Kr.; Mankar, Raju B.; Kulkarni, B. D. (Fluid Phase Equilibria, 2009)
Phase equilibrium and stability problems are of crucial importance in simulation, design and optimization of several separation processes. Recently, these problems have been solved using minimization of Gibbs free energy, using global optimization techniques. In this paper, repulsive particle swarm (RPS), a recent global optimization technique is explored for the Solution of phase stability and phase equilibrium. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid equilibria; Phase equilibrium; Phase stability analysis; Repulsive particle swarm method

Design of decanter in heterogeneous azeotropic distillation column by minimizing Gibbs free energy - Rahman, Imran; Ubaidullah, S.; Das, Anwesh Kr. (Asia-Pacific Journal of Chemical Engineering, 2013)
In this paper, liquid-liquid equilibrium in decanter of heterogeneous azeotropic distillation is solved by minimizing Gibbs free energy, by using global optimization technique. The azeotropic distillation column is modeled by solving material balance, equilibrium and summation equations, and repulsive particle swarm optimization (RPSO), a stochastic global optimization formalism, is employed to predict stable steady state solution in decanter. To verify the performance of the RPSO algorithm, it is compared with equation solving method for liquid-liquid equilibria by considering two azeotropic systems, namely (1) benzene-ethanol-water and (2) furfural-water. The proposed methodology shows feasibility of the RPSO algorithm in predicting liquid-liquid equilibrium in decanter of heterogeneous azeotropic distillation. (c) 2013 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: decanter; Gibbs free energy; heterogeneous azeotropic distillation; liquid-liquid equilibrium; Optimization; repulsive particle swarm optimization method